Construction drawing practice Part 3. Recommendations for symbols and other graphic conventions (BSI, 1987)
Engineering drawings, Architectural drawings, Drawings, Technical drawing, CONSTRUCTION, Plans, Graphic representation, Graphic symbols, Symbols, Construction systems, Construction systems parts, Structural systems, Construction materials, Landscaping, Windows, Doors, Ducts (building services), Pipework systems, Air-conditioning equipment, Lighting systems, Communication equipment, Sanitary appliances, Water supply and waste systems (buildings), Electric wiring systems